Pengembangan Aplikasi Perangkat Bergerak berbasis Firebase untuk Startup Pet Runner - Alvin Ariesta Wiyanto; Agi Putra Kharisma; Fais Al Huda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Pet Runner is a startup founded by several students of the Faculty of Veterinary Medicine, Brawijaya University. Pet Runner provides grooming services, health consulting and veterinary goods. In practice, Pet Runner uses the WhatsApp application to communicate with customers in determining schedules for grooming and ordering pet needs. As time goes by, the Pet Runner startup business experienced several problems, namely the limited number of WhatsApp accounts used so that the acceptance of customer requests became slower and the calculation of transactions and recording of customer data took longer due to the increase in the number of transactions. Firebase-based android mobile application development is the right solution because the majority of customers are android users and firebase can solve data processing problems with data integration. Application development is carried out using the waterfall software process model. The testing techniques used are scenario-based testing for functional testing and system usability scale (SUS) for non-functional testing. The results of scenario-based testing show a success rate of 100% with all test results valid. The score interpretation from SUS stated that the application is in Good application category for Adjective Ratings, obtained Grade C Scale and in Acceptable category in the Acceptability Ranges.